2021
DOI: 10.1101/2021.03.23.21254101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tools for measuring sexual and reproductive health and rights (SRHR) indicators in humanitarian settings

Abstract: Background: Effective measurement of all health indicators and especially SRHR is difficult in humanitarian settings. Displacement and insecurity due to conflict, natural disasters, and epidemics place women and girls at higher risk of SRHR-related morbidity and mortality and reduce the coverage of essential SRHR services. This scoping review describes the measurement tools, methods, and indicators used to measure SRHR coverage and outcome indicators in humanitarian settings in the past 15 years and presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It is necessary to have a specific, valid, and reliable instrument to study the sexual and reproductive health status of women with educable intellectual disability and to assess the related health service programs. A review of studies showed that although the World Health Organization has defined the domains of sexual and reproductive health, but there is no standard tool in this area and The available tools are specifically designed for different women such as conflict-affected women, women with specific diseases, women with breast cancer, and so on [ 15 , 16 ]. Also, the results of studies have shown that one of the barriers against sexual health provision for people with intellectual disability is the lack of a valid Sexual and Reproductive Health Assessment Scale for this group [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to have a specific, valid, and reliable instrument to study the sexual and reproductive health status of women with educable intellectual disability and to assess the related health service programs. A review of studies showed that although the World Health Organization has defined the domains of sexual and reproductive health, but there is no standard tool in this area and The available tools are specifically designed for different women such as conflict-affected women, women with specific diseases, women with breast cancer, and so on [ 15 , 16 ]. Also, the results of studies have shown that one of the barriers against sexual health provision for people with intellectual disability is the lack of a valid Sexual and Reproductive Health Assessment Scale for this group [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%